ARTISTIC INTERPRETATION OF THE POWER AND MAGIC OF THE WORD IN THE STORY OF USMON AZIM "GOOSE" - Jurayev Hakim Ibragimovich (International Journal of Literature and Language Studies, 2026)
This article examines the aesthetic nature, power, and magical properties of the artistic word in the short story "G'oz" (The Goose) by the People's Poet of Uzbekistan, Usmon Azim. It also explores the evolutionary development of epic traditions in contemporary Uzbek prose. Built upon the foundation of national mythological thinking and the ideological-artistic layers of the folk heroic epic "Alpamysh," the study analyzes the author's skill in creating a bakhshi-style (bardic) tone. The philosophy and tragic essence that form the core of the story reveal the magic and power of the word, as well as human will, the inevitability of fate, and issues of national honor.